2006
DOI: 10.1093/ps/85.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters from Univariate and Bivariate Analyses of Egg and Weight Traits in Japanese Quail

Abstract: Fully pedigreed records of a Japanese quail population were analyzed for genetic parameters of egg and BW traits. A restricted maximum likelihood (REML) procedure was applied in univariate and bivariate analyses. Quantitative genetic analyses, including maternal effects, were carried out on the records of 947 male and 861 female birds (total = 1,808). The traits were analyzed with bird as a random factor to fit the additive direct effect, bird being the individual for which the trait was recorded, namely hen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
18
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 16 publications
11
18
6
1
Order By: Relevance
“…This might be due to missing maternal genetic effects in their analyses. Saatci et al (2006) found that BW 0 had the lowest direct heritability and the highest maternal heritability among performance traits in Japanese quail that is in agreement with the results of the current study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This might be due to missing maternal genetic effects in their analyses. Saatci et al (2006) found that BW 0 had the lowest direct heritability and the highest maternal heritability among performance traits in Japanese quail that is in agreement with the results of the current study.…”
Section: Resultssupporting
confidence: 92%
“…However, Saatci et al (2006) reported that maternal effects are not important for EW in Japanese quail. The maternal genetic and environmental effects are not relevant for ASM.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This LW42 heritability estimate is higher than that obtained by Saatci et al (2006), who reported 0.15. In another study, Shokoohmand et al (2007) reported heritability estimates for different strains as 0.48, 0.50 and 0.72.…”
Section: Discussioncontrasting
confidence: 72%
“…It can be transitory but can also persist throughout life and be fulfilled through a great variety of biological mechanisms. Maternal effects in birds are different from those of mammals because any maternal effect on chicks, incubated artificially, must be the residual effect of dam reflected in egg characteristics at laying (Saatci et al, 2006). Willham (1980) emphasizes that knowledge of the type and relative importance of the genetic variation attributed to the maternal effect and, especially, to the type and magnitude of the genetic correlation between the direct and maternal additive effects of the traits is of high economic importance in the elaboration of breeding programs, where an evaluation of this effect is then necessary in each specific situation.…”
Section: Introductionmentioning
confidence: 99%